2014
DOI: 10.1155/2014/231258
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Japanese Medicine Daikenchuto Improves Functional Constipation in Poststroke Patients

Abstract: Poststroke patients with functional constipation, assessed by the Rome III criteria, from 6 hospitals were recruited in a study on the effects of the traditional Japanese medicine Daikenchuto (DKT) on constipation. Thirty-four patients (17 men and 17 women; mean age: 78.1 ± 11.6 years) were randomly assigned to 2 groups; all patients received conventional therapy for constipation, and patients in the DKT group received 15 g/day of DKT for 4 weeks. Constipation scoring system (CSS) points and the gas volume sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Daikenchuto can be used to treat patients with pain or cold sensations in the abdomen, and those who cannot eat due to nausea. Numata et al (2014b) reported that daikenchuto alleviated functional constipation in post-stroke patients. A subscale analysis showed that daikenchuto significantly improved constipation scores.…”
Section: Functional Abdominal Pain or Constipationmentioning
confidence: 99%
“…Daikenchuto can be used to treat patients with pain or cold sensations in the abdomen, and those who cannot eat due to nausea. Numata et al (2014b) reported that daikenchuto alleviated functional constipation in post-stroke patients. A subscale analysis showed that daikenchuto significantly improved constipation scores.…”
Section: Functional Abdominal Pain or Constipationmentioning
confidence: 99%
“…[17][18][19][20] DKT significantly reduced gas volume and improved functional constipation in post stroke patients. 21 On the other hand, a study about female functional constipation patients indicated that there are no effect treatment with oral DKT on colonic transit, rectal sensation, and stool frequency. 22 Moreover, the 15 g/day dose was associated with lower rectal first sensation threshold and gas threshold.…”
Section: Introductionmentioning
confidence: 99%
“…DKT is prescribed for abdominal pain with feeling cold and abdominal fullness. Clinical trials showed that DKT improves functional constipation in post-stroke patients (Numata et al 2014) and improves bowel movement after total gastrectomy for gastric cancer (Yoshikawa et al 2015). On the other hand, YKS is prescribed for neurosis, insomnia, and irritability in frailty.…”
Section: Discussionmentioning
confidence: 99%